Upaya Meningkatkan Hasil Belajar Fisika Melalui Model Pembelajaran Kooperatif Tipe Snowball Throwing Siswa Kelas VII SMP Negeri 17 Halmahera Selatan - Ernawati Muhtar (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is a classroom action research which aims to find out the efforts to improve the physics learning outcomes of class VII students of SMP Negeri 17 Halmahera Selatan through the snowball throwing cooperative learning model. The subjects of this study were 35 people. Action research carried out in 2 cycles. Cycle I actions include plans (planning), action (action), observation and evaluation (observation and evaluation), and reflection (reflection). Cycle II action is a follow-up and modification of cycle I. The success criterion is mastery of the concept of achieving the specified KKM, namely 70 individually and 65% classically. Research data obtained by giving a learning achievement test at the end of each cycle. The results of the study are described based on the acquisition of mastery of concept data in the form of learning outcomes for each cycle. The average value of concept mastery increased from 61.57 in cycle I to 72.29 in cycle II, in other words, the KKM in cycle I had not yet been completed to the KKM in cycle II. The conclusion of the research is an effort to improve physics learning outcomes for class VII students of SMP Negeri 17 South Halmahera through the snowball throwing cooperative learning model.